A complexidade do habitat e a variação individual na dieta e na morfologia de uma espécie de peixe associada à macrófitas. - Cardozo, Ana Lúcia Paz (2020)
Generalist species can be composed of specialist individuals, who use a small part of the population's niche. This process is known as individual specialization and can involve changes in diet and morphology. In this study, we hypothesized that individual variations in the diet and morphology of fish associated with macrophytes are related to the habitat’s complexity and greater levels of individual specialization will be found in the intermediate levels of macrophyte biomass. Fish and macrophytes were sampled in 30 multispecific macrophytes stands with different biomasses in a 13.7 km stretch of the rio Baía (Paraná River floodplain). Habitat complexity was assessed using the biomass of aquatic macrophytes (five stands with low biomass, five with intermediate biomass and five with high biomass were selected) and the fish species used in this study was Moenkhausia forestii. The individuals' diet was evaluated using the volumetric method, and the morphology through 18 linear measurements and six area measurements. To assess individual specialization in the diet, the Specialization Index (IS) and the NODF nesting index were used. Individual morphological specialization was assessed using ecomorphological diversity for each level of macrophyte biomass. Correlations between diet and morphology were assessed using the Mantel test. IS and NODF values indicated greater individual specialization in the diet in macrophytes stands with low biomass. The greatest individual morphological specialization was found in macrophytes stands with intermediate biomasses. The Mantel test showed that there was no significant correlation between diet and morphology. The individual specialization of M. forestii diet is related to the increase in competition, mainly intraspecific, intensified by the low availability of resources in low biomass stands. Morphological specialization, in turn, is related to greater availability and accessibility to resources within the intermediate biomass stands, where there are ideal conditions for increasing richness and abundance of resources and little structural complexity when compared to high biomass stands.